MOOC INITIATIVE: A TECHNOLOGY ENHANCED LEARNING IN 21 CENTURY AT HIGHER LEARNING INSTITUTIONS - Hafiza Haron; Supyan Hussin; Ahmad Rizal Mohd Yusof; Hafidzan Yusof (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
eLearning is a medium which is commonly implemented to provide learning module between instructor and learner through distance. In this era of digital technology, learning should be simplified, practical and can be provided in a holistic manner. eLearning is costeffective as compared to traditional forms of learning. The reason for this price reduction is because learning through this mode happens quickly and easily. A lot of training time is reduced with respect to trainers, travel, course materials, and accommodation. Surprisingly, most institutions provide the method of distance learning instead of physical classroom or faceto-face as a modern strategy in the learning environment. But yet, institutions need to prepare all sorts of things in order to take the challenges. In Malaysia, the MOOC initiative has been implemented a few years ago as a blended learning method and continued until now especially in Higher Learning Institutions. The technology of MOOC has sparkling the learning concept into a very interesting medium of learning between learner and instructor. Thus, the Khan eight-dimensional framework has been applied in this study in order to discuss the MOOC initiatives, including the brief history of MOOC, technological structure and learning design as a new technology for enhanced learning in the 21st century and beyond.